História e cultura dos povos indígenas do Brasil na educação : implicações da Lei nº 11.645/08 no referencial curricular da rede pública estadual de Roraima para o ensino médio - Matos, Rachel Pinheiro de (2017)
The research aims to analyze the proposals for approaching indigenous culture and history included in the 2012 High School Curricular Framework of Roraima state-government schools (RECEM/RR) after the promulgation of Statute N. 11.645/08. The need to understand and debate this theme arises from the obligation to comply with the statute in reference to RECEM/RR. The understanding of the different meanings attributed to the concepts of multiculturalism and interculturality, from the perspective of the curricular referential, is necessary, since it allows a new rethink that ensures the production of new strategies of insertion of approaches on the indigenous theme in the classroom. The possibilities of RECEM/RR and its conceptual approaches about the theme within the subject of history were discussed. Methodologically, the bibliographic study was combined with documentary analysis on the subject using content analysis with pre-established categories to achieve the objectives proposed in this research.